Extending Object-Oriented Frameworks with Aspects for Enabling Automatic Support for Domain-Specic Modeling - Santos, André L. (2007)
In the context of framework-based development, Domain-Specic Modeling (DSM) is a paradigm that raises the level of abstraction of application engineering. Using a Domain-Specic Modeling Language (DSML), applications are described by domain concepts in a model from which the application code is generated. This paper presents an approach for automating the construction of a DSM infrastructure for an object-oriented framework, where a DSML and a code generator for building applications are automatically derived. The approach is able to signicantly reduce the cost of adopting and evolving a DSM infrastructure. The high degree of automation is possible by enhancing frameworks with an additional layer of specialization modules, relying on our previous work on framework specialization aspects. The approach was implemented in our ALFAMA tool, and validated by a case study on the Eclipse RCP